Pre-Employment Card (Kartu Prakerja) In The Middle Of A Pandemic Review From The Concept Of Justice And Welfare - Risma Dewi Hermawan; Aris Prio Agus Santoso; Gempar Putra (Universitas PGRI Madiun, 2021)
The Covid 19 pandemic that attacked the industrial world of the Indonesian which resulted in the termination of employment by several companies so that the government had implemented policies including by issuing the Pre-Employment Card (Kartu Prakerja) Program to overcome unemployment and create welfare and social justice, but in the practice there are still people who have not received a pre-employment card. The problem in this research is how to implement the pre-employment card in terms of the concept of welfare and justice. The research uses a statute approach method. The research focuses more on library data, namely research carried out on secondary data which includes Indonesia Constitution, the 5th principle of the Pancasila, namely